Application of a Validated HPLC Method for the Determination of Resveratrol, Ferulic Acid, Quercetin, Retinol, and α-Tocopherol in a Cold Cream—Permeability Study - Athanasia Karavalasi; Sofia Almpani; Panagiota Tserkezou; Konstantina Chachlioutaki; Georgios Kamaris; Catherine K. Markopoulou (Applied Sciences)
Due to the rapid increase in the use of anti-aging cosmetic products, there is a need to develop valid analytical methods to control their quality. The present work deals with the development and validation of a new chromatographic method for the quantitative determination of five lipophilic components (resveratrol, ferulic acid, quercetin, retinol, and α-tocopherol), with anti-aging properties, in a cold cream (w/o). For the HPLC-UV separation of the active ingredients, an HS, Discovery® Supelco (Supelco Inc., Bellefonte, PA, USA), C18 column (25 cm × 4.6 mm), 5 μm (at 40 °C) was used as a stationary phase while a binary system of A: Acetonitrile with formic acid 0.2% and B: H2O with formic acid 0.2%, in gradient elution (flow 1.5 mL·min−1), was used as mobile. The analytical method was validated according to ICH guidelines Q2(R2), where linearity (r2 ≥ 0.998), selectivity, precision (% recovery 97.1–101.9), and accuracy (%RSD < 2) were evaluated. The processing of the samples for the recovery of the five analytes from the cream was investigated by experimental design methodology and the cross D-optimal technique (% recovery 98.5–102.9, %RSD < 2%, n = 5). Finally, the same analysis was applied to study the transdermal penetration of the active ingredients incorporated in cold cream (over a period of 8 h). Their behavior was compared with the corresponding one in suspension using Franz cells in a vertical arrangement. The new method is considered reliable for the analysis of the anti-aging product.